MANAJEMEN KEPALA SEKOLAH DALAM MENINGKATKAN KUALITAS PEMBELAJARAN PPKn DI SMA NEGERI 5 KOTA TERNATE - Hasyim, Rustam; Noho, Julfikar (Universitas Khairun, 2023)
The main problem in this thesis is the implementation of school principal management in an effort to improve the quality of Civics learning and the factors that become obstacles for school principals in efforts to improve the quality of Civics learning. The formulation of the problems in this panel were 1) how is the management of school principals in improving the quality of Civics learning, 2) what obstacles arise when carrying out principal management in improving the quality of Civics learning. The purpose of this research is to describe the principal's management and the principal's constraints in improving the quality of civics learning at SMA Negeri 5 Kota Ternate. The method used in this research is descriptive qualitative research using data collection instruments in the form of observation methods, interviews and documentation methods. The data sources in this study were school principals, vice principals, Civics teachers and students. Data analysis techniques used in this study are data reduction, data presentation 2 and conclusions. The research data show (1) principal management in improving the quality of Civics learning in schools namely (a) vision and mission-based management, (b) service-based management and (c) performance-based management. (2) The management constraints of school principals in improving the quality of Civics learning are (a) the teacher's lack of understanding in the use of teaching materials (b) the change of curriculum from K-13 to independent learning (c) the teacher's lack of skill in carrying out the learning process in class and (d) ) lack of interest in learning students in the classroom